Caspase-Mediated Apoptosis in Neuronal Excitotoxicity Triggered by Nitric Oxide - Leist, Marcel; Volbracht, Christiane; Kühnle, Simone; Fava, Eugenio; Ferrando-May, Elisa; Nicotera, Pierluigi (My University, 1997)
BACKGROUND: Excitotoxicity and excess generation of nitric oxide (NO) are believed to be fundamental mechanisms in many acute and chronic neurodegenerative disorders. Disturbance of Ca2+ homeostasis and protein nitration/nitrosylation are key features in such conditions. Recently, a family of proteases collectively known as caspases has been implicated as common executor of a variety of death signals. In addition, overactivation of poly-(ADP-ribose) polymerase (PARP) has been observed in neuronal excitotoxicity. We therefore designed this study to investigate whether triggering of caspase activity and/or activation of PARP played a role in cerebellar granule cell (CGC) apoptosis elicited by peroxynitrite (ONOO-) or NO donors. MATERIALS AND METHODS: CGC from wild-type or PARP -/- mice were exposed to various nitric oxide donors. Caspase activation and its implications for membrane alterations, Ca2+ homeostasis, intracellular proteolysis, chromatin degradation, and cell death were investigated. RESULTS: CGC exposed to NO donors undergo apoptosis, which is mediated by excess synaptic release of excitotoxic mediators. This excitotoxic mechanism differs from direct NO toxicity in some other neuronal populations and does not involve PARP activation. Inhibition of caspases with different peptide substrates prevented cell death and the related features, including intracellular proteolysis, chromatin breakdown, and translocation of phosphatidylserine to the outer surface of the cell membrane. Increased Ca2+ influx following N-methyl-D-aspartate (NMDA) receptor (NMDA-R) activation was not inhibited by caspase inhibitors. CONCLUSIONS: In CGC, NO donors elicit apoptosis by a mechanism involving excitotoxic mediators, Ca2+ overload, and subsequent activation of caspases.
Keywords: 570